PENCEGAHAN KECELAKAAN KERJA SAAT BERKENDARA MELALUI PENYULUHAN DAN PEMBAGIAN BUKU SAKU PADA SOPIR BENTOR DI KELURAHAN ANRONG APPAKA - A. Muflihah Darwis; Hermalia Putri; Rizky Burty Aryanti; Masitha Masitha; Onestin Bintang Paembonan; Nur Amaliah Tuwo; Nindya Wirasistha (STAI Darul Qalam Tangerang, 2023)
Work accident is an event related to work that can cause injury or illness, and can even cause death. From the data obtained in the Anrong Appaka Village, as many as 4.6% had experienced work injuries, 3.3% had experienced work accidents, and 8.1% had experienced work-related health problems and most of these occurred in residents who worked as conventional motorcycle taxi drivers or bumped into them. In overcoming this problem, interventions are carried out in preventing accidents while driving. The activity was carried out by providing counseling accompanied by distribution of pocket books on accident prevention while driving. This activity was carried out in the RW 1-4 area of ​​Anrong Appaka Village. This counseling is carried out by visiting conventional or bentor motorcycle taxi drivers. The method used is the lecture and discussion method with pocket book educational media. This activity was preceded and ended with a pre test and post test. At the end of the activity, pocket books were distributed related to accident prevention while driving and personal protective equipment (PPE) in the form of masks and gloves. The results of this activity indicate that there is an increase in the knowledge of bump drivers related to accident prevention while driving